2016
DOI: 10.1080/09585192.2015.1136672
|View full text |Cite
|
Sign up to set email alerts
|

Employee perceptions of HRM and well-being in nonprofit organizations: unpacking the unintended

Abstract: Adopting a process-based HRM lens, this study addresses how nonprofit workers perceive their HR practices and the ways in which these perceptions of HRM impact their wellbeing. Drawing on a multiple case study of eight social services NPOs in the UK, the impact of the employment relationship on the psychological, social and physical dimensions of wellbeing is examined in this climate of austerity. The findings highlight the increasing precariousness of this employment relationship alongside relatively weak HR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 47 publications
7
80
0
2
Order By: Relevance
“…Moreover, there is considerable debate on the role of social well‐being (e.g., trust, social support, fairness) in the causal chain between HRM, health/happiness well‐being and performance. While some studies have considered it at the same level as the other two dimensions of well‐being (e.g., Kooij et al, ; Baluch, ), others consider it a linking pin between HRM and health/happiness well‐being (e.g., Gould‐Williams, ; Kroon et al, ) or even as a moderator explaining when HRM affects health/happiness well‐being (e.g., Alfes et al ., ; Zhang et al ., ). Hence, we would encourage future research to include all three dimensions, yet focus on teasing out the exact causal role of the three dimensions and/or their potential interplay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is considerable debate on the role of social well‐being (e.g., trust, social support, fairness) in the causal chain between HRM, health/happiness well‐being and performance. While some studies have considered it at the same level as the other two dimensions of well‐being (e.g., Kooij et al, ; Baluch, ), others consider it a linking pin between HRM and health/happiness well‐being (e.g., Gould‐Williams, ; Kroon et al, ) or even as a moderator explaining when HRM affects health/happiness well‐being (e.g., Alfes et al ., ; Zhang et al ., ). Hence, we would encourage future research to include all three dimensions, yet focus on teasing out the exact causal role of the three dimensions and/or their potential interplay.…”
Section: Discussionmentioning
confidence: 99%
“…Building on Grant et al . 's () model, HRM research typically considers one or more of three types of well‐being: happiness (e.g., job satisfaction, commitment), health (e.g., stress, exhaustion) and social (e.g., trust, social support) well‐being (e.g., Baluch, ; Heffernan and Dundon, ; Veld and Alfes, ). In their review, Van de Voorde et al .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, De Winne et al 2013concluded that different sub-dimensions had different relationships with key stakeholders' perceptions of the role of HR, as defined by Ulrich (1997). Baluch (2017) found that, across multiple case studies, distinctiveness was high, yet consensus and consistency were low, suggesting that a broad overarching measure of HRSS may hide these nuances.…”
Section: The Relationships Among Consensus Consistency and Distinctmentioning
confidence: 99%
“…In general, studies show that employee-perceived HR strength is associated with positive employee outcomes such as organizational commitment (Farndale & Kelliher, 2013), job satisfaction (Heffernan & Dundon, 2016), vigor (Li et al, 2011), well-being (Baluch, 2017), task performance (Redmond, 2013), creativity (Ehrnrooth & Bjorkman, 2012), organizational citizenship behavior (Frenkel, Restubog, & Bednall, 2012), HR effectiveness (De Winne, Delmotte, Gilbert, & Sels, 2013), and organizational performance (Pereira & Gomes, 2012) while being negatively related to turnover intentions (Li et al, 2011) and negative emotions (Frenkel, Li, et al, 2012).…”
Section: Empirical Findingsmentioning
confidence: 99%